2014
DOI: 10.1371/journal.pone.0092340
|View full text |Cite
|
Sign up to set email alerts
|

Increased Complement C1q Level Marks Active Disease in Human Tuberculosis

Abstract: BackgroundComplement functions as an important host defense system and complement C5 and C7 have been implicated in immunopathology of tuberculosis. However, little is known about the role of other complement components in tuberculosis.MethodsComplement gene expression in peripheral blood mononuclear cells of tuberculosis patients and controls were determined using whole genome transcriptional microarray assays. The mRNA and protein levels of three C1q components, C1qA, C1qB, and C1qC, were further validated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
92
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(102 citation statements)
references
References 43 publications
7
92
1
1
Order By: Relevance
“…1I) (21). In TB patients undergoing chemotherapy (18, 20), SIRT1 mRNA levels increased after 2 to 3 months of therapy and reached levels comparable with those observed in healthy/latent TB individuals by the sixth month of treatment (Fig. 1J and fig.…”
Section: Resultssupporting
confidence: 61%
“…1I) (21). In TB patients undergoing chemotherapy (18, 20), SIRT1 mRNA levels increased after 2 to 3 months of therapy and reached levels comparable with those observed in healthy/latent TB individuals by the sixth month of treatment (Fig. 1J and fig.…”
Section: Resultssupporting
confidence: 61%
“…We observed an increase in C1q serum concentration in comparison to our healthy controls, which can be attributed to reactive upregulation by the tumor process as observed in infectious diseases as active tuberculosis and bacterial meningitis (Cai et al, 2014;Mook-Kanamori et al, 2014).…”
Section: Discussionsupporting
confidence: 52%
“…Complement and IgG binding of live M.tb h37Rv increases the number of viable intracellular bacilli, rather than reduce bacterial load which would be expected if antibody-dependant complement-mediated destruction occurred in TB [86]. This is in keeping with the previously mentioned activation of C1q that could be enhancing uptake of bacilli into their intracellular niche [20].…”
Section: Introductionsupporting
confidence: 60%
“…Fcγr1A binds antibody principally of the IgG1 and IgG3 subtype and is expressed mainly in macrophages and dendritic cells [19]. The expression of complement C1q, which forms immune complexes with immunoglobulin, is also elevated during active TB and is associated with increased disease severity [17], [20]. Further analysis of transcription studies have shown TRIM21, a recently identified intracellular antibody receptor, to also be elevated in disease [21].…”
Section: Introductionmentioning
confidence: 99%